Developing Conducive Sustainable Outdoor Learning (CSOL) : The Impact Of Natural Environment On Student's Ability - Nurakmal, Abdullah@ Goh Tuo Ho; Norngainy, Mohd Tawil; Mirrahmi, Seyedehzahra; Che-Ani, A. I.; Utaberta, Nangkula (Elsevier Science, Ltd., 2011)
Natural environments have a potential for encouraging students' physical health and psychological well being in schools. The green area are recognize to promote physical activity, which include a better designing the feature of landscaping for positive youth development. This paper explores how outdoor learning access to nature has two aims to sustainable this programs school gardens which improves the factors of psychological health and effective functioning between positive and negative behaviors and also to provide natural environment to enhance physical health, reduce health inequalities by supporting physical activities, directly advantage to growing body and also opportunities to encourage better nutrition for students.